Comparing Acute Bouts of Sagittal Plane Progression Foam Rolling vs. Frontal Plane Progression Foam Rolling. Issue 8 (August 2015) - Peacock, Corey A.; Krein, Darren D.; Antonio, Jose; Sanders, Gabriel J.; Silver, Tobin A.; Colas, Megan
Abstract : Abstract: Peacock, CA, Krein, DD, Antonio, J, Sanders, GJ, Silver, TA, and Colas, M. Comparing acute bouts of sagittal plane progression foam rolling vs. frontal plane progression foam rolling. J Strength Cond Res 29(8): 2310–2315, 2015—Many strength and conditioning professionals have included the use of foam rolling devices within a warm-up routine prior to both training and competition. Multiple studies have investigated foam rolling in regards to performance, flexibility, and rehabilitation; however, additional research is necessary in supporting the topic. Furthermore, as multiple foam rolling progressions exist, researching differences that may result from each is required. To investigate differences in foam rolling progressions, 16 athletically trained males underwent a 2-condition within-subjects protocol comparing the differences of 2 common foam rolling progressions in regards to performance testing. The 2 conditions included a foam rolling progression targeting the mediolateral axis of the body (FRml) and foam rolling progression targeting the anteroposterior axis (FRap). Each was administered in adjunct with a full-body dynamic warm-up. After each rolling progression, subjects performed National Football League combine drills, flexibility, and subjective scaling measures. The data demonstrated that FRml was effective at improving flexibility ( p ⩽ 0.05) when compared with FRap. No other differences existed between progressions.